Assessment of Pain and Quality of Life in Lichtenstein Hernia Repair Using a New Monofilament PTFE Mesh: Comparison of Suture vs. Fibrin-Sealant Mesh Fixation - Fortelny, René H.; Petter-Puchner, Alexander H.; Redl, Heinz; May, Christopher; Pospischil, Wolfgang; Glaser, Karl (Frontiers in Surgery, 2014)
Background: Inguinal hernia repair is one of the most common operations in general surgery. The Lichtenstein tension-free operation has become the gold standard in open inguinal hernia repair. Despite the low recurrence rates, pain and discomfort remain a problem for a large number of patients. The aim of this study was to compare suture fixation vs. fibrin sealing by using a new monofilament PTFE mesh, i.e. the Infinit® mesh by W. L. Gore & Associates. Methods: This study was designed as a controlled prospective single-centre two cohort study. A total of 38 patients were enrolled and operated in Lichtenstein technique either standard suture mesh fixation or fibrin sealant mesh fixation were used as described in the TIMELI trial. Primary outcome parameters were postoperative complications with the new mesh (i.e. seroma, infection), pain and quality of life evaluated by the VAS and the SF-36 questionnaire. Secondary outcome was recurrence assessed by ultrasound and physical examination. Follow-up time was 1 year. Results: Significantly less postoperative pain was reported in the fibrin sealant group compared to the suture group at 6 weeks (P=0.035), 6 months (P=0.023) and 1 year (P=0.011) postoperatively. Additionally trends towards a higher postoperative quality of life, a faster surgical procedure and a shorter hospital stay were seen in the fibrin sealant group. Conclusion: Fibrin sealant mesh fixation in Lichtenstein hernioplasty effectively reduces acute and chronic postoperative pain. Monofilament, macro-porous, knitted PTFE meshes seem to be a practicable alternative to commonly used polypropylene meshes in open inguinal hernia repair.